Formulasi Sediaan Sheet Mask Ekstrak Etanol Daun Pegagan (Centella asiatica (L.) Urb) sebagai Pelembab Kulit Wajah - Monica Suryani; Suharyanisa Suharyanisa; Ferdinand Paulus Ginting; Syarifah Roslianizar; Widya Fitri (Lembaga Pengembangan Kinerja Dosen, 2024)
Centella asiatica leaves contain active compounds such as alkaloids, flavonoids, saponins, and tannins, which are secondary metabolites. A sheet mask is a practical cosmetic facial treatment that does not require rinsing and is effective in moisturizing the skin. This study aims to determine the formulation of a sheet mask preparation. The ethanol extract of Centella asiatica leaves meets the physical quality evaluation criteria for the preparation. The experimental formulation method involves creating a sheet mask composed of various components including Centella asiatica leaf extract, glycerin, propylene glycol, xanthan gum, PEG-40 hydrogenated castor oil, nipagin, 96% ethanol, fragrance (Green tea), aquadest, sheet mask base, and foil bag. The research includes the characterization of the raw material, phytochemical screening of the extract, and formulation into sheet masks with concentrations of 2%, 4%, and 6%, followed by moisturizing testing using a skin analyzer. The evaluation of the preparation includes organoleptic tests, homogeneity, physical stability, viscosity, pH value, irritation testing, and hedonic testing. The characterization results show a water content of 3.46%, water-soluble extract content of 31.38%, ethanol-soluble extract content of 11.96%, total ash content of 8.41%, and acid-insoluble ash content of 1.09%. Phytochemical screening results show positive for alkaloids, flavonoids, saponins, tannins, and steroids. The study indicates that the ethanol extract of Centella asiatica can be formulated into a homogeneous and stable sheet mask preparation. The pH of the preparation meets the requirement with a value of 4.5-6.5, which is relatively safe for facial skin. The preparation does not cause irritation, with viscosity testing meeting the requirement of 250-1150 cp. The moisturizing test shows that a 6% Centella asiatica extract concentration provides the best moisturizing effect, and the most preferred formulation is F3 with a preference percentage of 38.12%. The average moisture values are F0 (Blank) 25.64%, F1 (2%) 33.26%, F2 (4%) 39.18%, and F3 (6%) 38.12%. Overall, it can be concluded that Centella asiatica extract can be formulated into a sheet mask with effective moisturizing capability for the facial skin.